Dynamic SDN controller placement based on latency in LEO satellite network - Zhenzhen HAN; Guofeng ZHAO; Chuan XU; Wentao ZHOU; Yangyang ZHOU (Tongxin xuebao)
In view of the problem of large network latency when the controller synchronized information to maintain the global network view,the latency-based SDN controller on-demand placement scheme was proposed.Firstly,the satellite subnet division method based on redundant coverage was designed according to the relative velocity of satellite and terminal.Then,the controller placement model was established by analyzing the response latency of the satellite distributed control.Finally,the controller placement problem was transformed into the soft capacitated facility location problem,and the approximation algorithm was designed to solve the model.The experimental results show that the proposed scheme can optimize network latency while meeting networking coverage demands.